Use of infographics to develop speaking skills of engineering students at English classes - Nina S. Shvaikina; Alexander A. Popel (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки, 2022)
Introduction of infographics into tertiary education became widespread during COVID-19 pandemic as the latter triggered a fundamental transition from conventional education to online one. This new format of teaching immediately revealed a few difficulties, such as poor attendance of students, lack of relevant technologies and equipment as well as inability of most educational institutions to respond to these challenges properly. Together with it, we have also discovered that students found it uneasy to learn new material, however, as we believe, it might be improved by introducing new technologies into teaching methodology which can be used both in online and classroom work for example, to follow up the material which has already been learned online. One of these technologies is infographics. The purpose of this paper is to familiarize readers with infographics as a tool and explain how inforgraphics may contribute to building English speaking skills at technical university. The object of the study in hand is the process of building English speaking skills of students studying at engineering faculties (industrial and civil engineering and construction and technological faculty). The subject of the work is use of infographics to build English speaking skills of students from these faculties in ELT. The practical value of this study is to show how infographics-based exercises could be implemented into English classes for first-year students who study the language at technical university. The research novelty of this study lies in the fact that infographics as a way of visual presentation of various textual, statistical information, data and knowledge is used as a means of teaching a foreign language at the stage of higher education. The results of the research can then be used to teach English to bachelors studying a wide range of engineering degrees, or as part of a refreshing course for non-linguistic masters. In addition, it should be noted that infographics can be used both for classroom and independent work of students.